Mimetic words and lexicalization patterns in a Japanese novel and its English translation / Ng Kar Pek - Ng , Kar Pek (2017)
Sound symbolic words exist in a wide variety of languages in the world, featuring a special class of words that shows a direct linkage between non-lexical sounds and meanings, recognized as mimetic words in Japanese. Generally, these mimetic words imitate the sounds of humans, animals, motions and natural phenomena, describe the manner or appearance of somebody or something, and are even capable to represent something more abstract such as people‟s feelings and emotions. Cognitive linguist, Leonard Talmy suggests that all languages in the world can be divided into two major typological groups, classified as either Satellite-framed languages or Verb-framed languages, where the main distinction relates to the conflation of Path of motion (Path) and Manner of motion (Manner) in the verb root. Utilizing Talmy‟s theory of lexicalization patterns, in conjunction with Sugiyama‟s research, which focuses on Manner expressions in the Japanese language, the present study identifies Manner expression and how it is embedded in Japanese and English by investigating mimetic words extracted from a Japanese novel, Norwegian Wood by Haruki Murakami, in comparison to its English text, translated by Jay Rubin. This study is carried out in three stages. First, the identified mimetic words are categorized into five classification groups. Second, the translation patterns of the mimetic words in their corresponding texts in English are examined. Finally, mimetic words are analyzed based on Talmy‟s interpretation of the binary typological framework through demonstration of examples, followed by a detailed description. The analysis shows that Japanese mimetic words frequently function as adverbial expressions to modify the verb, and to add an extra description to the meaning of the verb. In many cases, when translated into English, Manner is conflated in the verb and the Path of motion is expressed separately in a satellite. Although some data demonstrate other types of lexicalization patterns in English and Japanese, the present study supports Talmy‟s binary typology.